2012
DOI: 10.1074/jbc.m111.312769
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Protein-tyrosine Phosphatase α (PTPα) Increases Proliferation and Delays Maturation of Oligodendrocyte Progenitor Cells

Abstract: Background: Development of mature myelinating oligodendrocytes requires the co-ordinated migration, proliferation, and differentiation of oligodendrocyte progenitor cells (OPCs). Results: OPCs lacking PTP␣ show enhanced proliferation and altered activity and/or expression of several signaling molecules. Conclusion: PTP␣-dependent signaling limits OPC proliferation. Significance: This provides insight into the molecular events that promote the cessation of proliferation to position OPCs for differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Ranjan and Hudson found that PTP inhibitors decreased OL differentiation, and Ptpre , together with other PTP, was expressed in differentiating CG4 cells ( 18 ). Other PTPs have a role in OL maturation and myelination; Ptpa loss increased OPC proliferation ( 52 ); Ptprz knock out mice did not recover from EAE as well as controls and remyelination in MS plaques was associated with an upregulation of PTPRZ ( 53 ); also, hypomyelination was observed in Ptpre knock out mice ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ranjan and Hudson found that PTP inhibitors decreased OL differentiation, and Ptpre , together with other PTP, was expressed in differentiating CG4 cells ( 18 ). Other PTPs have a role in OL maturation and myelination; Ptpa loss increased OPC proliferation ( 52 ); Ptprz knock out mice did not recover from EAE as well as controls and remyelination in MS plaques was associated with an upregulation of PTPRZ ( 53 ); also, hypomyelination was observed in Ptpre knock out mice ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cultures of PTPα-/- OPCs have enhanced proliferation and survival and reduced growth factor dependence. PTPα-/- mice have increased oligodendrocyte lineage cells in the embryonic forebrain and delayed OPC development, with fewer mature oligodendrocytes in the early postnatal corpus callosum (Wang et al, 2012). In contrast, PTPβ/ζ negatively regulates proliferation as well as oligodendrocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…PTPβ/ζ-deficient mice have increased proliferation and early differentiation of OPCs in both the brain and optic nerve. At P10, PTPβ/ζ- /- mice have more myelinated axons in the corpus callosum, though normal levels by 3 months of age (Kuboyama et al, 2012; Wang et al, 2012). PTPε, on the other hand, appears to promote oligodendrocyte differentiation and myelination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from our laboratory has shown that PTPα regulates Cdc42 activation in a variety of signaling and cell contexts, notably including integrin-induced signaling in fibroblasts ( Samayawardhena and Pallen, 2008 ; Wang et al. , 2009 , 2012 ; Sun et al. , 2012 ).…”
Section: Discussionmentioning
confidence: 99%